Analisis Implementasi Corporate Social Responsibility Pada Perusahaan Berlabel Syariah di Bursa Efek Indonesia - Ferry Khusnul Mubarok (MediaTrend, 2019)
This study aims to identify the implementation of the Corporate Social Responsibility of Sharia Labeled Companies on the Indonesia Stock Exchange. This study uses a quantitative descriptive approach. The sample of this study is a sharia-labeled company listed on the Indonesia Stock Exchange, using a purposive sampling method. The results showed that the implementation of a sharia-labeled Corporate Social Responsibility company listed on the Indonesia Stock Exchange from 2009 to 2012 fulfilled all CSR disclosure indicators based on the Global Initiative Reporting. Companies labeled sharia express 6 aspects of CSR disclosure that cover economic, environmental, labor, human rights, social and product aspects.